Hydrogen liquefaction and storage: Recent progress and perspectives - ZHANG, TONGTONG (2023)
The global energy sector accounts for ∼75% of total greenhouse gas (GHG) emissions. Low-carbon energy carriers, such as hydrogen, are seen as necessary to enable an energy transition away from the current fossil-derived energy paradigm. Thus, the hydrogen economy concept is a key part of decarbonizing the global energy system. Hydrogen storage and transport are two of key elements of hydrogen economy. Hydrogen can be stored in various forms, including its gaseous, liquid, and solid states, as well as derived chemical molecules. Among these, liquid hydrogen, due to its high energy density, ambient storage pressure, high hydrogen purity (no contamination risks), and mature technology (stationary liquid hydrogen storage), is suitable for the transport of large-volumes of hydrogen over long distances and has gained increased attention in recent years. However, there are critical obstacles to the development of liquid hydrogen systems, namely an energy intensive liquefaction process (∼13.8 kWh/kgLH2) and high hydrogen boil-off losses (liquid hydrogen evaporation during storage, 1–5% per day). This review focuses on the current state of technology development related to the liquid hydrogen supply chain. Hydrogen liquefaction, cryogenic storage technologies, liquid hydrogen transmission methods and liquid hydrogen regasification processes are discussed in terms of current industrial applications and underlying technologies to understand the drivers and barriers for liquid hydrogen to become a commercially viable part of the emerging global hydrogen economy. A key finding of this technical review is that liquid hydrogen can play an important role in the hydrogen economy - as long as necessary technological transport and storage innovations are achieved in parallel to technology demonstrations and market development efforts by countries committed liquid hydrogen as part of their hydrogen strategies.